Roundtable: Imperial History by the Book: A Roundtable on John Darwin's The Empire Project. Reply. (2nd September 2015) - Darwin, John
Abstract: In an age when both the traditional book form and the world that the British Empire made are arguably in crisis, it is remarkable that big books on British imperialism abound. Contributors to this roundtable assess scale and genre as well as content in their discussion of the claims and impact of John Darwin's tome, The Empire Project . John Darwin's response is also included.